5/3x - 11/3 =
Now, combining the like terms on the left side, we get:
5/3x - 11/3 = -4/3
To isolate 5/3x, we now need to add 11/3 to both sides. This gives us:
5/3x - 11/3 + 11/3 = -4/3 + 11/3
Simplifying the left side further:
5/3x = -4/3 + 11/3
Now, adding -4/3 and 11/3, we have:
5/3x = 7/3
To solve for x, we can multiply both sides of the equation by the reciprocal of 5/3, which is 3/5:
(3/5)(5/3)x = (3/5)(7/3)
Simplifying further:
1x = 21/15
Now, simplifying 21/15:
x = 7/5
The equation 3/5x + 11/3 = -4/3 is solved as follows. Filling the correct numbers to complete the solution.
5/3x =
x =
Make sure to subtract 11/3 from both sides for 5/3x =
3 answers
No no so for
5/3x it says subtract 11/3 from both sides
x it says multiply both sides by 3:5, the reciprocal of 5/3 !
5/3x it says subtract 11/3 from both sides
x it says multiply both sides by 3:5, the reciprocal of 5/3 !
Apologies for the confusion. Let's correct the steps.
We have the equation 5/3x = -4/3 - 11/3.
To solve for x, we can start by subtracting 11/3 from both sides:
5/3x - 11/3 = -4/3 - 11/3.
Simplifying the right side:
5/3x - 11/3 = -15/3.
Now, to isolate x, we can multiply both sides of the equation by the reciprocal of 5/3, which is 3/5:
(3/5)(5/3)x = (3/5)(-15/3).
Simplifying:
1x = -9/5.
Therefore, the solution to the equation 3/5x + 11/3 = -4/3 is x = -9/5.
We have the equation 5/3x = -4/3 - 11/3.
To solve for x, we can start by subtracting 11/3 from both sides:
5/3x - 11/3 = -4/3 - 11/3.
Simplifying the right side:
5/3x - 11/3 = -15/3.
Now, to isolate x, we can multiply both sides of the equation by the reciprocal of 5/3, which is 3/5:
(3/5)(5/3)x = (3/5)(-15/3).
Simplifying:
1x = -9/5.
Therefore, the solution to the equation 3/5x + 11/3 = -4/3 is x = -9/5.